Improving the nutritive values of solid heavy phase to substitute corn in laying hens diet - Pasaribu, Tiurma; Sinurat, A.P.; Purwadaria, T.; Ketaren, P.P. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
Solid heavy phase (SHP), a by product material of palm oil factory obtained by ceramic filtration from liquid waste could be used as a feedstuff to replace corn in poultry diet. A series of experiment was carried out to improve nutrient value of the SHP by supplementation of enzymes and amino acids in order to increase the proportion of SHP to substitute corn in layer diet. There are three enzymes i.e.: Balitnak production (BS4), a commercial single enzyme (consist of mannanase) and comercial multienzymes were tested. All the enzymes were mixed with fresh SHP in different dose, dried and ground. The nutrient digestibility of these materials was measured in order to decide the optimum level of each enzyme. Based on this result, a feeding trial was carried out. Experimental diets were formulated to study the effect of substitusion of 25% or 50% corn with dried SHP or enzymes-treated SHP on the performances of the layers. The effect of methionine and lysine supplementation into diets contained high levels of SHP was also studied. Results showed that all enzymes studied could increase the energy (TME) of the SHP. BS4 enzyme and the commercial multienzimes, except single enzyme, also increase the true protein digestibility of the SHP. The optimum dose of each enzyme for each kg dry mater of SHP was 13.3 ml BS4, 2 g single enzyme and 3 g multienzymes. Substitution of 25% corn in layer diet with dried SHP or enzymes-treated SHP did not significantly impair the performances (hen-day egg production and FCR) of layers. However, substitution of 50% corn with SHP + multienzymes or SHP + single enzyme significantly impaired the performances of the layers. Addition of methionine and lysine amino acids restored the performance of the hens fed with SHP + commercial multienzyimes, but not those fed with high levels of SHP + commercial single enzyme. Substitution of 50% corn with SHP + BS4 enzime did not significantly impaire the performance of layers and therefore, addition of amino acids into the diet was not required. Substitution of 25% or 50% corn with dried SHP or enzymes-treated SHP did not affect the egg quality (HU, yolk color index and shell thickness). It is concluded that solid heavy phase (SHP) could be used to substitute 25 to 50% corn in layer diet, especially when the SHP was treated with BS4 enzyme. Key Words: Solid Heavy Phase, Enzymes, Amino Acids, Layer